Unique Combination of Diamond–Blackfan Anemia and Lynch Syndrome in Adult Female: A Case Report - Tsukanov, Aleksey S.; Pikunov, Dmitriy Y.; Shubin, Vitaly P.; Barinov, Aleksey A.; Kashnikov, Vladimir N.; Shelygin, Yuri A.; Kaprin, Andrey D.; Filonenko, Elena V.; Sidorov, Dmitriy V.; Maschan, Aleksey A.; Novichkova, Galina A.; Yasko, Liudmila A.; et al. (Frontiers in Oncology, 2021)
We present an extremely rare clinical case of a 38-year-old Russian patient with multiple malignant neoplasms of the uterus and colon caused by genetically confirmed two hereditary diseases: Diamond–Blackfan anemia and Lynch syndrome. Molecular genetic research carried out by various methods (NGS, Sanger sequencing, aCGH, and MLPA) revealed a pathogenic nonsense variant in the MSH6 gene: NM_000179.2: c.742C>T, p.(Arg248Ter), as well as a new deletion of the chromosome 15’s locus with the capture of 82,662,932–84,816,747 bp interval, including the complete sequence of the RPS17 gene. The lack of expediency of studying microsatellite instability in endometrial tumors using standard mononucleotide markers NR21, NR24, NR27, BAT25, BAT26 was demonstrated. The estimated prevalence of patients with combination of Diamond–Blackfan anemia and Lynch syndrome in the world is one per 480 million people.